Analisis Strategi Pemasaran (7P) pada Masa Pandemi Covid-19 di Kolam Renang Lembah Manah Girikulon Kabupaten Magelang Tahun 2021 - Afifah Dwi Ramadhanti; Supriyono Supriyono (Universitas Negeri Semarang, 2022)
The purpose of this study was to determine the marketing strategy (7P) carried out during the Covid-19 pandemic at the Lembah Manah Girikulon Swimming Pool, Magelang Regency in 2021. This study used a descriptive qualitative research approach. The targets in this study were swimming pool managers, pool employees, and visitors at the Valley Manah Girikulon swimming pool, Magelang Regency. Data collection techniques can be done by observation, interviews, and documentation. The results of this study indicate that the Lembah Manah Girikulon Swimming Pool has a swimming pool product that continues to operate during the Covid-19 pandemic which carries the theme of the outdoors. Prices are affordable for the general public and students. The place is easy to reach. Employees have been provided with training on basic water rescue. Promotion is done through social media. The physical environment (physical evidence) is extensive, the spatial arrangement is neat, and is in an environment that is still beautiful. Operational process according to health protocol. The marketing strategy (7P) of Lembah Manah Girikulon Swimming Pool is going well. The manager of the Lembah Manah Girikulon Swimming Pool is expected to continue to plan a good marketing strategy, always pay attention to market conditions in order to remain competitive and attract visitors.